The first step would be to subtract 1 from both sides, leaving you with 5x = 10.
Answer:
I guess it is the Answer C
Answer: 40
Step-by-step explanation:
Answer:
4
Step-by-step explanation:
Yeah if you don't know this one... you're... special.
The average rate of change of a function f(x) in an interval, a < x < b is given by
![\frac{f(b) - f(a)}{b - a}](https://tex.z-dn.net/?f=%5Cfrac%7Bf%28b%29%20-%20f%28a%29%7D%7Bb%20-%20a%7D)
Given q(x) = (x + 3)^2
1.) The average rate of change of q(x) in the interval -6 ≤ x ≤ -4 is given by
![\frac{q(-4)-q(-6)}{-4-(-6)} = \frac{(-4+3)^2-(-6+3)^2}{-4+6} = \frac{1-9}{2} = \frac{-8}{2} =-4](https://tex.z-dn.net/?f=%20%5Cfrac%7Bq%28-4%29-q%28-6%29%7D%7B-4-%28-6%29%7D%20%3D%20%5Cfrac%7B%28-4%2B3%29%5E2-%28-6%2B3%29%5E2%7D%7B-4%2B6%7D%20%3D%20%5Cfrac%7B1-9%7D%7B2%7D%20%3D%20%5Cfrac%7B-8%7D%7B2%7D%20%3D-4)
2.) The average rate of change of q(x) in the interval -3 ≤ x ≤ 0 is given by
![\frac{q(0)-q(-3)}{0-(-3)} = \frac{(0+3)^2-(-3+3)^2}{0+3} = \frac{9-0}{3} = \frac{9}{3} =3](https://tex.z-dn.net/?f=%20%5Cfrac%7Bq%280%29-q%28-3%29%7D%7B0-%28-3%29%7D%20%3D%20%5Cfrac%7B%280%2B3%29%5E2-%28-3%2B3%29%5E2%7D%7B0%2B3%7D%20%3D%20%5Cfrac%7B9-0%7D%7B3%7D%20%3D%20%5Cfrac%7B9%7D%7B3%7D%20%3D3)
3.) The average rate of change of q(x) in the interval -6 ≤ x ≤ -3 is given by
![\frac{q(-3)-q(-6)}{-3-(-6)} = \frac{(-3+3)^2-(-6+3)^2}{-3+6} = \frac{0-9}{3} = \frac{-9}{3} =-3](https://tex.z-dn.net/?f=%20%5Cfrac%7Bq%28-3%29-q%28-6%29%7D%7B-3-%28-6%29%7D%20%3D%20%5Cfrac%7B%28-3%2B3%29%5E2-%28-6%2B3%29%5E2%7D%7B-3%2B6%7D%20%3D%20%5Cfrac%7B0-9%7D%7B3%7D%20%3D%20%5Cfrac%7B-9%7D%7B3%7D%20%3D-3)
4.) The average rate of change of q(x) in the interval -3 ≤ x ≤ -2 is given by
![\frac{q(-2)-q(-3)}{-2-(-3)} = \frac{(-2+3)^2-(-3+3)^2}{-2+3} = \frac{1-0}{1} = \frac{1}{1} =1](https://tex.z-dn.net/?f=%20%5Cfrac%7Bq%28-2%29-q%28-3%29%7D%7B-2-%28-3%29%7D%20%3D%20%5Cfrac%7B%28-2%2B3%29%5E2-%28-3%2B3%29%5E2%7D%7B-2%2B3%7D%20%3D%20%5Cfrac%7B1-0%7D%7B1%7D%20%3D%20%5Cfrac%7B1%7D%7B1%7D%20%3D1)
5.) The average rate of change of q(x) in the interval -4 ≤ x ≤ -3 is given by
![\frac{q(-3)-q(-4)}{-3-(-4)} = \frac{(-3+3)^2-(-4+3)^2}{-3+4} = \frac{0-1}{1} = \frac{-1}{1} =-1](https://tex.z-dn.net/?f=%20%5Cfrac%7Bq%28-3%29-q%28-4%29%7D%7B-3-%28-4%29%7D%20%3D%20%5Cfrac%7B%28-3%2B3%29%5E2-%28-4%2B3%29%5E2%7D%7B-3%2B4%7D%20%3D%20%5Cfrac%7B0-1%7D%7B1%7D%20%3D%20%5Cfrac%7B-1%7D%7B1%7D%20%3D-1)
6.) The average rate of change of q(x) in the interval -6 ≤ x ≤ 0 is given by